The duties of the almoner (memorandum) - Mudd, Edith E.
1901-10-25 1901 1900s 5 pages change. This man was no loss to the Medical School. He returned to be examined and show how a fairly hopeful case can respond to treatment necessary for it. I have no doubt it will be said - "This is an exceptional case," although I am glad to say I have two more away now who seem as likely to do as well as he. But surely such possibilities show that the duties of an Almoner, cannot be limited to mere enquiry, and must aim at preventing waste and abuse on the lines I have indicated, by all possible means. When appointed Almoner to this Hospital I clearly stated my methods of working, and from the first said that in so far as I was able to judge, enquiry work must go hand in hand with relief work, to be in any way efficient. I have never deviated from this, except to be more and more convinced that I could do nothing at all without the help of extraneous Charities, and I am far from using the C.O.S alone. The work has keenly interested me. I have so far as lay in my power, endeavoured to study it from every side - from that of the Staff, the Medical School, the General Practitioner, and the Charitable Public, and I am satisfied in my own mind, that if this work on some such lines gained ground in other Hospitals, it should eventually lead to good results. I am, Gentleman, Your obedient Servant, Edith E. Mudd 378/IMSW/A/1/4/3a